UJI PERBANDINGAN ARANG SEKAM DENGAN KOMPOS KULIT KAKAO SEBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum.L) HIDROPONIK SISTEM WICK - Dodi, Ahmad; Seprido, Seprido; Pramana, Angga (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2018)
The purpose of this research to know the Comparison Charcoal Husk withcompost skin cacao as cropping about the media and crop production and production red onio (Allium ascalonicum.L) hydroponic wick system. This study has been implemented dikebun experiment faculty agricultural kuantan singingi islamic university. This research use random design complete ( ral ) non factorials, using various the comparison media (factors M) consisting of 5 standard treatment and 3 test. Treatment M1 ( Charcoal Husk ) M2 (compost skin cacao) M3 (Charcoal Husk + compost skin cacao) (1:3) M4 (compost skin cacao + Charcoal Husk) (2:2) M5 (Charcoal Husk + compost skin cacao) (3:1). There is a unit of experiments 15, any unit experiment consisting of 4 plants , 3 plants constituting sample plants. The result showed that comparison media Charcoal Husk with compost skin cacao give real impact give influence the real thing to all observation parameter. Observation plant height with the best results on treatment M5 with hight plant 35.71 cm. And have a real influence on observation parameter number of leaves 28.44 helai,gross weight 18.76 g dan dry weight 14.79.Keywords : Red Onion, Charcoal Husk, Compost Skin Cacao, Hidroponics